The Panama canal expansion mega project : a case study and stakeholder´s analysis - Guardia, Eugenia (2015)
As globalization increases integration, a new playing field is emerging which is driving the need for operational efficiencies and alignment of complementary capabilities among countries to build sustainable models and integrated offerings. As demands increase, companies are turning to effective project management as means to control operations and countries are increasing the amount of mega projects to boost their competitiveness and global footprint. Given the scale, complexity, political nature, multicultural makeup, and high level of visibility; mega projects rely on successful stakeholder management to effectively manage its operational, tactical, and strategic levels to execute their mission. This paper examines the success drivers of mega projects and presents an in depth stakeholder assessment of the Panama Canal Expansion mega project to identify the perceived value to its stakeholder community. The stakeholder categories include: the Panama Canal Authority, subcontractors executing the expansion project, customers of the canal in Panama and U.S., as well as the communities surrounding the Panama Canal and ports in the U.S. East Coast. The conclusion of this paper captures the relationship between the effective stakeholder engagement from the Panama Canal Authority, the perceived value of the Panamanian stakeholders, and compares it to U.S. based mega projects being executed simultaneously to allow the U.S. East Coast ports to accommodate increased cargo volumes.